C-2 (E)-4-(Styryl)aniline substituted diphenylpyrimidine derivatives (Sty-DPPYs) as specific kinase inhibitors targeting clinical resistance related EGFRT790M mutant. Issue 10 (15th May 2017) - Song, Anran; Zhang, Jianbin; Ge, Yang; Wang, Changyuan; Meng, Qiang; Tang, Zeyao; Peng, Jinyong; Liu, Kexin; Li, Yanxia; Ma, Xiaodong
Graphical abstract: Highlights: C -2 ( E )-4-(Styryl)aniline-substitued diphenylpyrimidine derivatives (Sty-DPPYs) as potent EGFR T790M inhibitors. Inhibitor10e displayed strong potency against the EGFR T790M enzyme (IC50  = 11.0 nM). Inhibitor10e has a higher SI value (SI = 49.0) than rociletinib (SI = 21.4). Inhibitor10e has low toxicity against the normal HBE cell (IC50  = 22.48 μM). Abstract: With the aim to overcome the drug resistance induced by the EGFR T790M mutation (EGFR T790M ), herein, a family of diphenylpyrimidine derivatives (Sty-DPPYs) bearing a C-2 ( E )-4-(styryl)aniline functionality were designed and synthesized as potential EGFR T790M inhibitors. Among them, the compound10e displayed strong potency against the EGFR T790M enzyme, with the IC50 of 11.0 nM. Compound10e also showed a higher SI value (SI = 49.0) than rociletinib (SI = 21.4), indicating its less side effect. In addition, compound10e could effectively inhibit the proliferation of H1975 cells harboring the EGFR T790M mutation, within the concentration of 2.91 μM. Significantly, compound10e has low toxicity against the normal HBE cell (IC50  = 22.48 μM). This work provided new insights into the discovery of potent and selective inhibitor against EGFR T790M over wild-type (EGFR WT ).